Eksplorasi Hubungan Tingkat Pengetahuan Terhadap Kepatuhan Terapi Pasien Hipertensi di UPT Puskesmas Tanjung Batu Kabupaten Karimun - Maulina, Novia; Luthfi, Fitrati Hasanah; Inayatilah, Fidia Rizkiah; muslikh, Faisal akhmal (Journal of Islamic Medicine, 2025)
Background: Hypertension is a condition where blood pressure exceeds normal levels (120/80mmHg), with systolic blood pressure above 140 mmHg and diastolic blood pressure above 90mmHg. Termed as the "silent killer," hypertension often manifests without symptoms and is a leading cause of death in Indonesia. The prevalence of hypertension in the Riau Islands Province reached 25.85% in 2018, with Karimun Regency ranking second. Objectif: This study aims to assess the relationship between knowledge and adherence to antihypertensive medication among hypertensive patients at UPT Puskesmas Tanjung Batu, Karimun, in 2022. Methods: This observational study employs a Cross-sectional design. Data were collected from March to May 2022 from 90 respondents using a questionnaire. The sampling method used was consecutive sampling. Data analysis involved univariate and bivariate analyses with the Spearman rank test (significance level 0.005). Results: The majority of respondents were female (71%), aged 46-55 years (43%), with an educational background of elementary school (62%). On average, they had suffered from hypertension for less than 5 years (56%), and the primary source of information was from doctors (81%). Knowledge level was sufficient (49%), while medication adherence was low (83%). Statistical analysis indicated a significant relationship (p=0.001) and alignment between knowledge and adherence among hypertensive patients at UPT Puskesmas Tanjung Batu, Karimun, with a moderate correlation (r=0.343). Conclusion: There is a significant relationship between knowledge and adherence to antihypertensive medication among hypertensive patients.